UPAYA PENINGKATAN HASIL BELAJAR IPS MATERI INTERAKSI ANTAR NEGARA ASIA DAN NEGARA LAINNYA MELALUI MODEL MAKE A MATCH: STUDI PENELITIAN TINDAKAN KELAS - Siti Mungawanah (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2023)
This study aims to describe the implementation of the make a match learning model to improve social studies learning outcomes on the material of interactions between Asian countries and other countries in class 9E SMP Negeri 1 Tempuran in the 2022/2023 academic year. This research is class action research (PTK). Each cycle consists of three stages of activity, namely planning, implementation of action and observation, and reflection. The subjects of this study were students of class 9E SMP Negeri 1 Tempuran Magelang Regency with a total of 31 students. Data collection in this study used teacher and student activity observation sheets and written tests. Data analysis techniques used were descriptive qualitative and descriptive quantitative with percentages. The results showed an increase in social studies learning outcomes on the material of interactions between Asian countries and other countries in students of class 9E SMP Negeri 1 Tempuran after the implementation of learning with the Make a Match learning model in cycle I on average was 78.065 after cycle II on average was 85.16. Behavioral changes that occur in class 9E students of SMP Negeri 1 Tempuran in the implementation of learning with the make a match learning model to improve social studies learning outcomes on the material of interactions between Asian countries and other countries, among others (a) students are better able to work together; (b) all students are more active and enthusiastic in learning; (c) students feel happy and not bored in participating in learning; (d) in learning activities students are more honest; (e) students are more disciplined and responsible.